HUBUNGAN KEKUATAN OTOT LENGAN BAHU DAN KELENTURAN OTOT PUNGGUNG DENGAN HASIL TOLAK PELURU PADA MAHASISWA PUTRA IIA PENJASKESREK ANGKATAN 2013 UNIVERSITAS RIAU - Fahrobi JH, Muhammad; Wijayanti, Ni Putu Nita; ', Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: The problem in this study originated from the observation that the authors found in the field, the results of student men's shot put IIA penjaskesrek 2013 University of Riau has yet to get the maximum repulsion. The purpose of this study was to determine the relationship of muscle strength and muscle tone arm shoulder back with the results of the men's shot put penjaskesrek II A 2013 University of Riau forces.The population in this study was student son penjaskesrek II A 2013 University of Riau, amounting to 38 people using the total sampling technique where all the population sampled, to obtain research data used expanding test dynamometer, muscle flexibility and rich with sit back and shot put results. Data were analyzed by simple and multiple product moment.Based on the analysis of the data found that the results obtained from the arm shoulder muscle strength have relations with the result of men's shot put at the students IIA penjaskesrek 2013 University of Riau. From the results obtained by the flexibility of the back muscles have a relationship with the results of men's shot put at the students IIA penjaskesrek 2013 University of Riau. There is a relationship together between muscle strength and muscle tone arm shoulder back against the results of men's shot put at the students IIA penjaskesrek 2013 University of Riau.Keywords: Arm shoulder muscle strength, muscle flexibility back, shot put results